2004
DOI: 10.1186/1471-2164-5-97
|View full text |Cite
|
Sign up to set email alerts
|

The association of Alu repeats with the generation of potential AU-rich elements (ARE) at 3' untranslated regions.

Abstract: Background: A significant portion (about 8% in the human genome) of mammalian mRNA sequences contains AU (Adenine and Uracil) rich elements or AREs at their 3' untranslated regions (UTR). These mRNA sequences are usually stable. However, an increasing number of observations have been made of unstable species, possibly depending on certain elements such as Alu repeats. ARE motifs are repeats of the tetramer AUUU and a monomer A at the end of the repeats ((AUUU) n A). The importance of AREs in biology is that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…The poly(T) sequence that exists in antisense Alu elements is the source of ~40% of identified 3′UTR AU-rich elements (AREs), which regulate mRNA half-life through the competitive binding of proteins that stabilize or destabilize the transcript (Fig. 3A) (45). Additionally, LINEs and SINEs can activate the function of microRNAs (miRNAs) by acting as promoters for miRNA synthesis or as miRNA-binding sites in target mRNAs (46, 47) (Fig.…”
Section: Regulation Of Rna Processingmentioning
confidence: 99%
“…The poly(T) sequence that exists in antisense Alu elements is the source of ~40% of identified 3′UTR AU-rich elements (AREs), which regulate mRNA half-life through the competitive binding of proteins that stabilize or destabilize the transcript (Fig. 3A) (45). Additionally, LINEs and SINEs can activate the function of microRNAs (miRNAs) by acting as promoters for miRNA synthesis or as miRNA-binding sites in target mRNAs (46, 47) (Fig.…”
Section: Regulation Of Rna Processingmentioning
confidence: 99%
“…In this connection, previous studies proposed a role of 3’UTR-embedded Alus in regulating mRNA stability. While Wilson et al [40] demonstrated that Alus at 3’UTR increase mRNA half-life, An et al [86] suggested that 3’UTR Alus could generate AU-rich elements that destabilize certain mRNAs. Other authors pointed to Alu RNAs embedded in 3’UTRs as microRNA targets that might influence gene expression [41].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the orientation of the Alus inside 3’UTRs relative to the gene sense might also have an effect in the genesis of PPs. The presence of antisense Alus, which are generators of AU-rich elements, or inverted Alus could modify the localization of the transcript in the cytoplasm [86, 89], maybe increasing the probability of binding the SRP9/14 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Primate specific Alu retrotransposons, which occupy ~11% of the human genome, are major players in this process (1,7). These provide non-canonical transcription factor binding sites and other regulatory sites that govern epigenetic modifications as well as provide cryptic splice sites that lead to alternative splicing or differential mRNA stability (5,(8)(9)(10)(11)(12)(13)(14). Alu-derived exons exhibit lineage specificity with high transcript inclusion levels and have much higher rates of evolution (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that transcript isoform dynamics i.e., the relative proportion of exonized versus non-exonized isoforms of a gene, could be modulated by these events in viral recovery and stress response (19,20). Besides, Alus provide substrates for other regulatory events such as gain of poly-A sites, AU-rich motifs and miRNA recognition elements (MREs) that can result in alternative polyadenylation, mRNA decay or translation stalling; and formation of specific secondary structures (9,(21)(22)(23)(24)(25). We have also reported that Alu-MREs can alter transcript isoform dynamics during stress response and some of these sites seem to be evolving in humans (20).In our earlier study on 3177 Alu-exonized genes, we reported the co-occurrence of cis Alu antisense and A-to-I editing at the level of single Alu exons in 319 genes.…”
mentioning
confidence: 99%